The world-mover - Smith, George O. (George Oliver), 1911-1981; Finlay, Virgil, 1914-1971 (Salt Lake City, UT : Project Gutenberg, 2023)
"The World-Mover" by George O. Smith is a science fiction novel written in the mid-20th century. The story revolves around Les Ackerman, a scientist who unwittingly triggers a catastrophic nuclear explosion, which leads to his being caught between two alternate realities$1 (Bone where he survives and one where he faces the consequences of his experiment. As he navigates these bizarre circumstances, he becomes the focal point for factions from both worlds that believe he holds the key to resolving their conflicts. At the start of the narrative, Les Ackerman is deeply engrossed in his research on a newly discovered transuranic element, Element X, when a nuclear incident propels him into a state of limbo, observing the chaos that ensues from the explosion he caused. Stranded between two realities, he witnesses the aftermath of the catastrophe, struggling to reconcile his existence with the fact that others perceive him as dead. The arrival of Tansie Lee introduces additional complexity, as she explains to him his critical role in the unfolding events and the necessity for his involvement to navigate the dual paths of existence stemming from his experiment. As he grapples with his newfound status, he also faces external pressures from various characters who have their own motivations regarding his fate and the fate of both worlds. (This is an automatically generated summary.)s
Release date is 2023-05-21
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Time travel -- Fiction; Man-woman relationships -- Fiction; Physicists -- Fiction; Transuranium elements -- Fiction